SWACAM and the Future of Self-Service: a TAM Study of Perceptions, Attitudes, and Intentions to Use - Artina Ningsih; Harmanda Berima Putra (Journal of Social Commerce, 2025)
This study aims to analyze customer acceptance of the SWACAM feature in the PLN Mobile application using the Technology Acceptance Model (TAM). Based on data from 181 postpaid customers at PLN UP3 Serpong, this research empirically investigates the impact of perceived ease of use and perceived usefulness on users' attitudes and their intention to use the SWACAM feature. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that both perceived ease of use and perceived usefulness significantly affect user attitudes and intentions. Attitude also mediates the relationship between perception and intention. These results provide practical insights for PLN to enhance the adoption of self-service technologies.